2004
DOI: 10.1097/01.ccm.0000126127.87484.2b
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C and ischemic stroke

Abstract: There is compelling evidence that ischemic stroke is an attractive target for therapy with APC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…The most striking effects of APC were visible on genes involved in the Bcl-2 family, which was also revealed in brain endothelial cells. 24 A study by Pirat et al also revealed an antiapoptotic effect of human APC after 20 minutes of ischemia and 2 hours of reperfusion, but an antiinflammatory effect on C-reactive protein or TNF-␣ levels was not visible possibly because of the short ischemic period used. 17 Direct effects of APC on neutrophil migration have been demonstrated in experimental models under conditions of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking effects of APC were visible on genes involved in the Bcl-2 family, which was also revealed in brain endothelial cells. 24 A study by Pirat et al also revealed an antiapoptotic effect of human APC after 20 minutes of ischemia and 2 hours of reperfusion, but an antiinflammatory effect on C-reactive protein or TNF-␣ levels was not visible possibly because of the short ischemic period used. 17 Direct effects of APC on neutrophil migration have been demonstrated in experimental models under conditions of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…103 The prospective epidemiologic Atherosclerosis Risk in Communities (ARIC) study reported that plasma protein C appeared protective against ischemic stroke (OR ϭ 0.65 [0.4-1.0]). 104 In murine models of focal cerebral ischemia, APC provided remarkable anti-inflammatory and neuroprotective effects.…”
Section: Apc In Ischemic Strokementioning
confidence: 99%
“…[91][92][93] Indeed, in a murine model of focal cerebral ischemia, administration of aPC reduced cerebrovascular and brain damage by inhibiting infiltration of leukocytes in For personal use only. on May 12, 2018.…”
Section: The Pc System In Vascular Inflammationmentioning
confidence: 99%